AlignRT® and Catalyst™ in whole‐breast radiotherapy with DIBH: Is IGRT still needed?. Issue 3 (12th March 2019) - Laaksomaa, Marko; Sarudis, Sebastian; Rossi, Maija; Lehtonen, Turkka; Pehkonen, Jani; Remes, Jenny; Luukkanen, Helmi; Skyttä, Tanja; Kapanen, Mika
Abstract: Purpose: Surface guided radiotherapy (SGRT) is reported as a feasible setup technique for whole‐breast radiotherapy in deep inspiration breath hold (DIBH), but position errors of bony structures related to deeper parts of the target are not fully known. The aim of this study was to estimate patient setup accuracy and margins obtained with two different SGRT workflows with and without daily kV‐ and/or MV‐based image guidance (IGRT). Methods: A total of 50 breast cancer patients were treated in DIBH, using SGRT for the patient setup, and IGRT for isocenter corrections. The patients were treated at two different departments, one using AlignRT ® (25 patients) and the other using Catalyst™ (25 patients). Inter‐fractional position errors were analyzed retrospectively in orthogonal and tangential setup images, and analyzed with and without IGRT. Results: In the orthogonal kV‐kV images, the systematic residual errors of the bony structures were ≤ 3 mm in both groups with SGRT‐only. When fine‐adjusted by daily IGRT, the errors decreased to ≤ 2 mm; except for the shoulder joint. The residual errors of the ribs in tangential images were between 1 and 2 mm with both workflows. The heart planning margins were between 3 and 7 mm. Conclusions: The frequency of IGRT may be considerably reduced with a well‐planned SGRT‐workflow for whole‐breast DIBH with residual errors ≤ 3 mm. This accuracy can be further improved with an IGRT scheme.